Resolution of Rac‐Bambuterol via Diastereoisomeric Salt Formation with o‐Chloromandelic Acid and Differences in the Enantiomers' Pharmacodynamical Effects in Guinea Pigs and Beagles. Issue 4 (25th January 2016) - Wu, Jie; Liu, Fei; Wang, Shanping; Wang, Hongjun; Liu, Qing; Song, Xinghan; Li, Junxiao; Xu, Ling; Tan, Wen
Abstract: In this study an enantioseparation method for rac‐bambuterol (5‐(2‐(tert‐butylamino)‐1‐hydroxyethyl)‐1, 3‐phenylene bis(dimethylcarbamate)) via diastereoisomeric salt formation with o‐chloromandelic acid was developed. The enantiomeric excess ( ee ) values and chemical purities of the desired products were confirmed by high‐performanceliquid chromatography (HPLC) using chiral stationary phase and reverse‐phase HPLC analyses, respectively. The ee values and the chemical purities both exceeded 99%. Animal experiments showed that (R)‐bambuterol was a potent inhibitor for histamine‐induced asthma reactions. (S)‐bambuterol was ineffective in relaxing the airways. Both enantiomers increased heart rates in beagles. Therefore, replacing rac‐bambuterol with (R)‐bambuterol could be beneficial for asthma patients. Chirality 28:306–312, 2016 . © 2016 Wiley Periodicals, Inc. Abstract :